PEMANFAATAN KOMPOS KULIT KAYU MANGIUM UNTUK MEDIA PERTUMBUHAN CENDAWAN MIKORIZA ARBUSKULA DAN BIBIT Acacia mangium Willd. - Sihati Suprapti; Erdy Santoso; Djarwanto; Maman Turjaman (BRIN Publishing, 2012)
Sterilized and unsterilized manginm bark which added with activators and composted for 30 days were used at a growth medium for mycorrhizal fungi and Acacia mangium seedlings. Degradation rate of the bark wus evaluated based on the changing content of organic carbon, total nitrogen, nutrient content, and its cation exchange capacity (CEC) Results showed that activators added on the compasting process of manpium bark reduced C/N ratio to 21.90 in sterilized bark and 25.30 in the ansterilized, respectively. The addition of actors tended to increase the nutrient content Le. N 0.82 -1.09%, P 0.22 -0.36%, and K. 0.36 -1.12%, and increase the value of CEC ints 31.3 to 32.7 me/100g Mycurrhizal colonization on medium means that composted mangium bark can be used both as growth and mycorrbizal carrier media. A high percentage of mycorrhizal colony was found in the medium made of sterilized mangium bark added with activators inoculated with Glomus sp. ir. 45%. The growth rate of A. mangium seedling on the mediume made of sterilized mangium bark added with activator tended to be bigher than that of the unsterilized bark. The highest growth was found on medium inoculated with Gigaspora sp., abile the largest stem diameter occurred on the medium inoculated with Glomus sp.